Cosmogony in the Perspective of the Prophet of Muhammad’s Utterances - Danusiri - (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2021)
The study reports on a version of the cosmogonic information amidst the various chronicle stories of the world's great tribes. The Prophet Muhammad's version of cosmogony has dimensions of transcendentalism. The version also contains the actual value of the Islamic faith, rather than just a myth. The study uses qualitative with library research, and the data were sourced from nine standard hadith books, at digital ‘Lidwa Pustaka-I’ Software ‘Kitab 9 Imam Hadith’ (2009). The study applied thematic and chronological methods to describe how the universe has begun, created a shape until the end of its existence. Allah has created the universe from ‘nothing’ into ‘existence’. Based on His mercy, pre-designed was pitch black at the beginning of the world’s creation. Light arose simultaneously with the process of the occurring part of the universe. The findings reveal that the entire contents of the universe designated as facilities for life where the earth is helpful for human life. At one point, nature will shrink because Allah grasps it, the layout of every celestial body changes completely, and its aftermath is unknown to humans. Abstrak: Kajian ini melaporkan informasi pada sebuah versi kosmogonik di tengah berbagai kisah kronik suku-suku besar dunia. Kosmogoni versi Nabi Muhammad SAW memiliki dimensi transendentalisme. Versi tersebut juga memuat nilai aktual dari akidah Islam, bukan sekedar mitos. Penelitian ini menggunakan kualitatif dengan studi kepustakaan, dan data bersumber dari sembilan kitab hadis standar, pada software digital 'Lidwa Pustaka-I' 'Kitab 9 Imam Hadith' (2009). Kajian ini menerapkan metode tematik dan kronologis untuk menggambarkan bagaimana alam semesta dimulai, diciptakan dan dibentuk hingga akhir keberadaannya. Allah telah menciptakan alam semesta dari 'tidak ada' menjadi 'ada'. Berdasarkan rahmat-Nya, pra-desain dalam keadaan gelap gulita pada awal penciptaan dunia. Cahaya muncul bersamaan dengan proses terjadinya alam semesta. Temuan penelitian ini mengungkapkan bahwa seluruh isi alam semesta ditetapkan sebagai fasilitas kehidupan dan bumi bermanfaat bagi kehidupan manusia. Pada suatu saat, alam akan menyusut karena Allah menggenggamnya, tata letak setiap benda angkasa berubah total, dan akibatnya tidak diketahui manusia. Kata-kata kunci: kosmogoni, perspektif, sabda Nabi